Praziquantel resistance in schistosomes: a brief report - Eastham, Gabriela; Fausnacht, Dane; Becker, Matthew H.; Gillen, Alan; Moore, William (Frontiers in Parasitology, 2024)
Schistosomiasis is a group of both acute and chronic parasitic trematode infections of the genus Schistosoma. Research into schistosomiasis has been minimal, leading to its classification as a neglected tropical disease, yet more than 140 million people are infected with schistosomes globally. There are no treatments available for early-stage infections, schistosomal dermatitis, or Katayama syndrome, other than symptomatic control with steroids and antihistamines, as the maturing organisms seem to be mostly resistant to typical antiparasitics. However, praziquantel (PZQ) has been the drug of choice for schistosomiasis for decades in the latter stages of the disease. Though it is effective against all three clinically relevant species, heavy reliance on PZQ has led to concerns of schistosome resistance, especially in areas that have implemented this drug in mass drug administration (MDA) programs. This article summarizes the available literature concerning the available evidence for and against a warranted concern for PZQ resistance, genomic studies in schistosomes, proposed mechanisms of resistance, and future research in alternative methods of schistosomiasis treatment.